+0  
 
0
337
1
avatar
I am having trouble solving this problem:
-6(5-2z)+5z=8z-3(16-3z)
Guest Feb 12, 2012
 #1
avatar+3077 
0
-6(5-2z)+5z=8z-3(16-3z)
-30+12z+5z=8z-48+9z
+12z+5z-8z-9z=30-48
0 = -18
and this is false
admin  Feb 12, 2012

29 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.